2022
DOI: 10.3390/jcm11030705
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Predictors of Prognosis in Patients with Traumatic Cerebral Haemorrhage: Retrospective Study

Abstract: We aimed to evaluate the relationship between neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), systemic inflammation index (SII), and Glasgow Coma Scale (GCS) score in patients with traumatic intracerebral haemorrhage (TICH). We retrospectively investigated 95 patients with TICH hospitalised at the Neurosurgery Department in Zielona Gora from January 2017 to March 2021. Routine blood tests were performed 5 h after injury. NRL and SII were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Routine blood tests to assess inflammatory processes are often useful in the early diagnosis of several diseases as well as in clinical prognosis in traumatic intracerebral haemorrhage [ 8 ]. The assessment of the basic parameters in the peripheral blood count, which is both inexpensive and easy to perform, provides us with information about changes in the numbers of lymphocytes, neutrophils, monocytes and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Routine blood tests to assess inflammatory processes are often useful in the early diagnosis of several diseases as well as in clinical prognosis in traumatic intracerebral haemorrhage [ 8 ]. The assessment of the basic parameters in the peripheral blood count, which is both inexpensive and easy to perform, provides us with information about changes in the numbers of lymphocytes, neutrophils, monocytes and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…The studies were assessed with appropriate guidelines to characterize their quality based on several criteria ( Table 1 ) [ 8 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. NOS scores of 7–9 were deemed sufficient for the study as it fell in the region of “high quality” study according to the NOS guidelines, including case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the secondary effects of TBI such as intracranial bleeding and increased intracranial pressure, neurosurgical intervention may be required to evacuate hematomas and/or relieve swelling with decompressive craniotomy [ 6 ]. Although the GCS score has been established as a relatively accurate prognostic indicator, it is a subjective measure that has been shown to have inter-observer variability [ 7 , 8 ]. Furthermore, GCS does not provide information regarding inflammatory processes within the brain that may cause acute deterioration in patients, thus there is a need to investigate a more objective prognostic measure of TBI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also suggested that the higher the SII, the worse the prognosis of patients with cerebral hemorrhage and cerebral venous thrombosis (CVT) ( 46 ). A study of 95 patients with traumatic intracerebral hemorrhage (TICH) showed that NLR and SII were significantly correlated with GCS scores and were promising predictors of clinical outcomes in patients with TICH ( 47 ). But so far, there are no studies on the predictive effect of SII in patients with severe craniocerebral trauma.…”
Section: Discussionmentioning
confidence: 99%